(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The abundance of tick populations in South Africa represents a probable risk for both animal and human health. Rickettsia spp. and Borrelia spp. are well-known agents of emerging human tick-borne infectious diseases worldwide. Nevertheless, the epidemiology of their infections has been underreported in South Africa. Therefore, this study aimed to profile zoonotic Rickettsia and Borrelia species from ticks infesting domesticated animals in the Eastern Cape, South Africa. Materials and Methods: Morphological and molecular identification techniques were conducted on 1,200 tick samples collected from domestic animals before screening for the target bacterial pathogens. The molecular identification of the tick samples was based on the amplification of the 12S rRNA mitochondrial Deoxyribonucleic acid. At the same time, those of Rickettsia and Borrelia species were carried out by amplifying fragments of gltA and ompB genes for Rickettsia and flaB gene for Borrelia spp. Thereafter, the positive amplicons for Rickettsia ompB were sequenced and further analyzed. Borrelia PCRs were negative; therefore, sequencing could not be performed. Results: Eight species of ticks belonging to three genera; Rhipicephalus, Amblyomma, and Haemaphysalis, were identified. A total of 27% (320/1,200) samples were confirmed positive for Rickettsia, of which 23% (74/320) were positive for ompB genes. Phylogenetic analysis of ompB revealed a high homology to rickettsial reference strains from GenBank, with no positive result for Borrelia. The generated sequences showed homology with R. africae-KX227790 (100%), R. parkeri-KY113111 (99.8%), R. peacockii (99.3%), and R. slovaca-JX683122 (99.1%) representative sequences in GenBank. Conclusion: The findings from this study revealed that ticks harbored Rickettsia species with possible zoonotic potential. Adv. Vet. Anim. Res., 11(2): 254-263, June 2024 http://doi.org/10.5455/javar.2024.k771